2019
DOI: 10.7189/jogh.09.010801
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Impact: iCCM as a strategy to save lives of children under five

Abstract: Background In 2013, the World Health Organization (WHO) launched the Rapid Access Expansion (RAcE) programme in the Democratic Republic of Congo, Malawi, Mozambique, Niger, and Nigeria to increase coverage of diagnostic, treatment, and referral services for malaria, pneumonia, and diarrhea among children ages 2-59 months. In 2017, a final evaluation of the six RAcE sites was conducted to determine whether the programme goal was reached. A key evaluation objective was to estimate the reduction in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Recent reports from the Rapid Access Expansion (RACE) programs in Nigeria have shown that care-seeking for fever from an appropriate provider increased from 78% to 94% following implementation of iCCM and that coverage with artemisinin-based combination therapies (ACTs) within 1 day of symptom onset increased from 57% to 74% amongst malaria-confirmed cases [6]. Evidence from these iCCM programs have shown a reduction of overall clinical disease symptoms and all-cause child mortality after implementation [6,7]. These are consistent with findings from other studies, including cluster randomised trials of community health worker (CHW) programs, showing a decrease in overall mortality after increasing diagnosis and treatment coverage for malaria and other diseases [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports from the Rapid Access Expansion (RACE) programs in Nigeria have shown that care-seeking for fever from an appropriate provider increased from 78% to 94% following implementation of iCCM and that coverage with artemisinin-based combination therapies (ACTs) within 1 day of symptom onset increased from 57% to 74% amongst malaria-confirmed cases [6]. Evidence from these iCCM programs have shown a reduction of overall clinical disease symptoms and all-cause child mortality after implementation [6,7]. These are consistent with findings from other studies, including cluster randomised trials of community health worker (CHW) programs, showing a decrease in overall mortality after increasing diagnosis and treatment coverage for malaria and other diseases [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“… 44 This has improved recently with substantial increases in evaluations done to generate country specific, and sometimes district or village specific clarifications for programme successes and failures. 15 24 40 45–55 M&E of iCCM, and broader strategies influencing child health outcomes, improves adaptation of programme structure and service delivery for populations to achieve the greatest impact from programme potential. 6 18 21 28 30 32 56 Evaluations can provide revelations in programme effectiveness or the lack thereof.…”
Section: Resultsmentioning
confidence: 99%
“…Various strategies were employed by the global community to scale-up effective child health interventions [ 9 , 10 ]. The integrated Community Case Management is effective in reducing under-five mortality if implemented with sufficient coverage [ 9 ]. Community health workers are able to manage common childhood illnesses outside health facilities, which include identifying and treating sick children at their homes.…”
Section: Introductionmentioning
confidence: 99%